Green-supporting factors, brown-penalising factors and the prudential framework a theoretical approach - Olli Castrén; Riccardo Russo (European Banking Authority (EBA), 2024)
Proposals to include adjustments such as brown penalising and green supporting factors in the prudential regulation are meant to direct bank lending towards environmentally friendly projects. However, such adjustments can blur the lines between prudential credit risk assessment and environmental objectives. Favouring green projects, although clearly socially responsible in the long term, may channel bank lending towards excessively risky assets in the short term and provide a distorted picture of the true financial health of the bank. We adopt a principal-agent approach to formalise this trade-off and highlight its impact on bank lending. We also show that - in the presence of investor pressures or uncertainty of green asset returns - banks could decide to redirect lending towards green projects without direct regulatory intervention as formulated in the pillar I framework.
Keywords: E50; D86; G28; Q58; 330; Prudential policy; climate risks; green finance; Walsh contract; climate change; green economy; monetary policy; financial risk; sustainable development; loan